Peran Guru BK Dalam Mengatasi Kesulitan Belajar Siswa Pecandu Game Online di SMA Negeri 4 Binjai - Risa Nur Fadilla; Sabrina Dwi Putri; Armirayati Pratiwi; Jadidi Jadidi; Dika Sahputra (Peneliti.net, 2023)
This study aims to determine the role of the greeting counseling teacher in overcoming the learning difficulties of online game addict students at SMA Negeri 4 Binjai. From the data collected, it is known what role the guidance and counseling teacher should take to overcome the learning difficulties of students who are addicted to online games in class X. The method used in this research is a qualitative method with a descriptive approach, data collection techniques were carried out through interview guidelines, observation guidelines and questionnaire distribution. The subjects of this research were school principals, guidance and counseling teachers and 25 class X students. The results of this study obtained the role of the guidance and counseling teacher in overcoming the learning difficulties of online game addict students at SMA Negeri 4 Binjai.